PENGARUH RASIO MOLAR SUBSTRAT DAN KONSENTRASI KATALIS PADA PEMBUATAN DECYL POLIGLIKOSIDA DARI D-GLUKOSA DAN DEKANOL - Rap Leanon, Walad Wirawan, Zuhrina Masyithah (Universitas Sumatera Utara, 2015)
There are two methods to produce alkyl polyglucoside (APG) which are direct method and indirect method. In this research, APG synthesize with direct method that involves by directly reacting d-glucose with decanol with molar ratio variation of d-glucose:decanol are 1:10; 2:10; 4:10 and 6:10 (mol GL/mol C10) and HCl concentration as catalyst variation are 0,5; 1; 1,5 dan 2 (% based on weight of d-glucose) in 3 hours with temperature reaction is 95 0C. Next process is neutralizing with strong base (NaOH) until pH value is about 8-10 then the aqueous solutions are distillated with vacuum distillation. This research analyze density, yield and wavelength. Decyl polyglycoside synthetic optimum results best density value is 1,05 gr/mL in molar ratio of d-glucose:decanol 2:10 (mol GL/mol C10) and catalyst concentration 0,5%. Best yield in molar ratio of d-glucose:decanol 2:10 (mol GL/mol C10) and catalyst consentration 1,5% (% based on weight of d-glucose) with yield value is 84,09 %. Wavelength analysis of ether and OH linkage with Fourier Transform Infrared (FT-IR) spectroscopy detected ether (COC) linkage at wavenumber 1032,33 cm-1 and OH groups detected at wavenumber 3365,21 cm-1.